Combined Broccoli Sprouts and Green Tea Polyphenols Contribute to the Prevention of Estrogen Receptor–Negative Mammary Cancer via Cell Cycle Arrest and Inducing Apoptosis in HER2/neu Mice - Li, Shizhao (J Nutr, 2020)
BACKGROUND: Aberrations in the regulation of cell proliferation perturb cellular homeostasis and lead to malignancies in which dysregulation of the cell cycle and suppressed apoptosis are 2 common phenomena. Combinatorial nutritional approaches could be efficacious in ameliorating these aberrations. OBJECTIVES: We sought to investigate the effect of dietary broccoli sprouts (BSp) and green tea polyphenol (GTP) administration on cell cycle progression and apoptosis in mammary tumors. METHODS: Forty female HER2/neu transgenic mice were randomly divided into 4 groups and treated with control, 26% BSp (wt:wt) in food, 0.5% GTPs (wt:vol) in drinking water, or combined BSp and GTPs from dams’ conception until their pups were killed at 29 wk of age. Pups’ tumor growth was monitored weekly for 27 wk. Tumor cell cycle– and apoptosis-related protein expression was measured. Data were analyzed with 2-factor or 3-factor (repeated-measures) ANOVA. RESULTS: Compared with the control group, BSp and/or GTPs decreased tumor incidence (P < 0.05) and combined BSp and GTPs synergistically [combination index (CIn) < 1] reduced tumor volume over time (P-time < 0.01). BSp and/or GTPs upregulated the expression of phosphatase and tension homolog, P16, and P53 (P < 0.05) and downregulated myelocytomatosis oncogene, Bmi1 polycomb ring finger oncogene, and telomerase reverse transcriptase (P < 0.05) compared with the control group. Combined BSp and GTPs synergistically (CIn < 1) downregulated the expression of cyclin B1, D1, and E1 and cyclin-dependent kinase 1, 2, and 4 (P < 0.05) compared with the control group. Moreover, combined BSp and GTPs induced apoptosis by regulating Bcl-2-associated X protein and B-cell lymphoma 2 (P < 0.05). BSp and/or GTPs also reduced the expression of DNA methyltransferase 1, 3A, and 3B and histone deacetylase 1 compared with the control group (P < 0.05). CONCLUSIONS: Collectively, lifelong BSp and GTP administration can prevent estrogen receptor–negative mammary tumorigenesis through cell cycle arrest and inducing apoptosis in HER2/neu mice.